Analisis Pengukuran Kinerja KCU Pintu Air dengan Menggunakan Metode Balanced Scorecard - Elya Maria Nitbani; Andreas Rangga; Yoseph Darius P. Rangga (Jurnal Akuntan Publik, 2024)
This study aims to determine the performance of KCU Pintu Air by using the balanced scorecard method. This research method is a quantitative descriptive method. The data in this study were obtained from documentation in the form of financial reports and distributing questionnaires. The population in this study was KCU Pintu Air with a sample of a financial perspective in the form of financial reports, a customer perspective with a sample of 44 members, an internal business process perspective and a growth and learning perspective with a sample of 27 employees. The findings of this study show that the performance of KCU Pintu Air when measured using the balanced scorecard method results in a rating scale of 0.2 which lies between 0-0.6 which indicates that the cooperative's performance is quite good. The results of perspective calculations in the balanced scorecard are financial perspective calculations with unfavorable results, this is because most of the PEARLS ratio calculation results are in the bad category. The customer perspective shows good results, which are obtained from indicators of member retention and member acquisition which experience fluctuations and indicators of member satisfaction as much as 79% of members are satisfied with cooperative services. The internal business process perspective shows very good results, which are obtained from the results of the questionnaire with an operational efficiency indicator of 80% and an indicator of competitive position of 83%, which means that the respondents stated that they were very satisfied. The growth and learning perspective shows good results obtained from the results of employee satisfaction indicators as much as 91% of employees who express attitudes towards very high satisfaction, employee retention indicators that show good results and employee productivity indicators that experience fluctuations during the study period.